Pengaruh Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Di Boncafe Pentacity Mall Balikpapan - Maharani, Mei Dita; Iswati, Iswati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the effect of Service Quality on Customer Satisfaction and Customer Loyalty. This research is conducted at Boncafe Pentacity Mall Balikpapan in 2024 where the researcher is face to face with the respondents. Respondents in this study are loyal visitors who visit more than once, the number of respondents in this study is set at 50 respondents by using Likert scale sampling technique to assess the variables under study. Data analysis was carried out through a series of statistical tests, including validity and reliability tests to ensure instrument reliability, as well as coefficient of determination analysis, multiple linear regression, t test, and F test to test the research hypothesis.The results of this study indicate that: There is a direct positive effect of Service Quality on Satisfaction. There is a direct positive effect of Satisfaction on Loyalty. There is a direct positive effect of Service Quality on Loyalty. There is an indirect positive effect of Service Quality on Loyalty.